Performance Enhancement of Nurses with Quality of Nursing Work Life Model - Pujiyanto, Tri Ismu; Hapsari, Shindi (International Journal of Psychosocial Rehabilitation, 2020)
Nurses are responsible for maintaining the optimal quality of care services. The quality of their work nurses affects service performance. The study aims to determine the improvement of nurses’ work through the quality of work-life models. The study used secondary data analysis to identify the nurses’ performance with intervention models that used Quasy design experiments with pre and post-test with the control group. The quality intervention of nurse care work is conducted for five days with a knowledge management method that includes socialization, externalization, combination and internalization. 102 samples were carried out with a random sampling of clusters based on where nurses provided nursing care. The analysis results of the difference in performance value of Nurse service between control group and intervention before t intervention = 8,145; p = 0.000, after intervention t = 13,024, and the difference between before and after the intervention t = 11,879; p = 0.000. Differences in the value of nursing work life between intervention groups and control groups were t = 6,321; p = 0.000 before the intervention, t = 9,422 after intervention, and the differences between the intervention group and the control group before and after the intervention were T = 8,282; p = 0.001. This research shows that the quality model of working life nurse affects nurses’ performance which can be seen from the performance of nursing care to the appropriate standards especially in nursing care and nurses’ satisfaction at work.